Antibacterial polymeric nanocomposites synthesized by in-situ photoreduction of silver ions without additives inside biocompatible hydrogel matrices based on N-isopropylacrylamide and derivatives - M. Monerris; M. Broglia; I. Yslas; C. Barbero; C. Rivarola (eXPRESS Polymer Letters)
Synthesis of antibacterial nanocomposite obtained by in-situ photoreduction of Ag+ ions impregnated inside a biocompatible hydrogel matrix is described. Hydrogel matrixes based on N-isopropylacrylamide (PNIPAM) and copolymers are synthesized by free radical polymerization in aqueous medium. The hydrogels are loaded with Ag+ ions and then silver nanoparticles (Ag-NPs) are obtained in-situ by application of UV light without using additives. Ag-NPs formation inside hydrogels is confirmed by UV–visible spectroscopy, scanning electronic microscopy (SEM) and transmission electronic microscopy (TEM). An extensive characterization of nanocomposites is performed by determining the partition coefficient of Ag+ ions before photoreduction, the Ag-NPs mass loaded per gram of hydrogel as a function of irradiation time, swelling capacity and volume phase transition temperature. Fourier Transform Infrared (FTIR) spectra indicate the loss of some functional groups of the polymer backbone during reduction of Ag+ ions whereas 13C NMR spectra do not show any change in the main carbon chain. Nanocomposites show antibacterial activity against Pseudomonas aeruginosas by release of Ag+ ions while Ag-NPs remain inside matrix. Reducing/stabilizing character of hydrogel and antibacterial activity of nanocomposite depend on the chemical composition of the matrix.